Assessing the Financial Performance of the Gorontalo Regency Health Office - Camelia Savitri Beu; Ilyas Lamuda; Wahyudin Hasan; Barmin R. Jusuf (LPPPIPublishing, 2026)
Assessing the Financial Performance of the Gorontalo Regency Health Office. (Supervised by Ilyas Lamuda as the Main Supervisor and Wahyudin Hasan as the co-supervisor). This study aims to assess the financial performance of the Gorontalo Regency Health Office by calculating effectiveness, efficiency, and operational ratios. The method used is a descriptive, quantitative method, utilizing the Budget Realization Report and the Annual Report. The data analysis technique uses regional financial ratio calculations. The results show that the financial performance of the Gorontalo Regency Health Office during the 2020-2024 period is effective. However, in terms of efficiency, program budget management is still categorized as less efficient. Meanwhile, in terms of operational ratios, the expenditure structure is still dominated by operational expenditures. This indicates the need for improvements in planning, budget control, and a more balanced expenditure structure to support the sustainable improvement in the quality of health services.